2017
DOI: 10.3390/su9040480
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Tourism and Hospitality Sector Electricity Consumption in Spanish Provinces (1999–2013)

Abstract: Abstract:The EU is committed to a 40% reduction in their domestic greenhouse gas emissions by 2030. In order to reach this ambitious target, new measures affecting all economic sectors would be needed. This paper focuses on the tourism sector. Using econometric panel data techniques, the relationships between tourist overnight stays and the hospitality sector electricity consumption is studied for the Spanish provinces during the period 1999-2013. With this aim, an Energy-Tourism Kuznets Curve hypothesis is te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Both developing and developed countries are focusing on the CO 2 reduction without affecting the sustainable development. Focusing on the tourism sector, Romero et al [17] investigated the link between tourists stay and the electricity consumption for Spain. The results indicated that the EKC hypothesis is not valid in the case of Spain during 1999-2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both developing and developed countries are focusing on the CO 2 reduction without affecting the sustainable development. Focusing on the tourism sector, Romero et al [17] investigated the link between tourists stay and the electricity consumption for Spain. The results indicated that the EKC hypothesis is not valid in the case of Spain during 1999-2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In that sense, the study by Ben Aissa et al [42] finds that international attraction and market competition have a direct influence on hotel efficiency, while other studies, such as those of Razumova et al [43] and Leonidou et al [44], indicate that hotels are more predisposed to implement effective green strategies when they have sufficient physical and financial resources. Therefore, as stated in Pablo-Romero et al [34], increasing the Hotel and Restaurant sector earnings through tourism stays increases, for example, the ease of implementing energy efficiency measures, thereby reducing energy use. Nevertheless, it is worth noting that some other papers also highlight that hotels that offer higher quality services use more energy [45][46][47], causing energy consumption growth.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, the nights spent at tourist accommodation establishments' series was used (sample number code tour_occ_ninat). Total overnight stays have been used before as a proxy to measure tourism, such as in the studies by Cortés-Jiménez and Pulina [50] and Gómez-Calero et al [51], and more recently in the study by Pablo-Romero et al [34]. Figures are expressed in overnight stays per inhabitants in natural logs.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations